Human Rights in the Training of Teachers. Paradigmatic Femicides in the Province of La Pampa, Argentina - Siderac, Silvia (2017)
This article gives an account of the experiment carried out on the basis of the photographic exhibition “The violence in focus. Three paradigmatic femicides in La Pampa" that was carried out in the interior of the educational community of the Faculty of Sciences at the National University of La Pampa (UNLPam), together with the feminist organization "Women for Solidarity" in the framework of a cultural program of the Ministry of Culture and Extension of the UNLPam. The people who took part in this activity were teachers of the Faculty of Sciences and students from various undergraduate courses. The objectives of the sample were to build an educational space in relation with human rights, to make visible the three femicides of Pampa society, to work in a collaborative manner by bringing together social actors of the university and the community, and to make this experience an instance for pedagogical training. A qualitative-designed methodology was implemented, and by means of pictures, university students from undergraduate courses worked with the theoretical categories of gender violence and different types of gender violence, compromise, and femicide; they worked in conjunction with high school students. The objective of this work was to carry out an experience that would integrate the university functions of teaching, research and extension on the basis of a so sensitive social issue such as the femicides in Argentina.